Application of MIKE FLOOD Model in Drainage Schemes for High-density Built-up Areas: Taking the Southern Region of Fuhai River in Shenzhen as an Example - YAN Hengheng; LU Qiaohui (Renmin Zhujiang)
To effectively solve the flooding problem in urban high-density built-up areas and accurately determine drainage schemes for these areas, this paper introduces the MIKE FLOOD model and takes the southern region of Fuhai River in Shenzhen as the research object. The study simulates and analyzes the waterlogging condition and river overtopping condition of the study area under flood-dominated and tide-dominated scenarios by current scheme, centralized drainage scheme and decentralized drainage scheme. The results show that: ①Under the flood-dominated and tide-dominated scenarios, there is local waterlogging in the study area. Under the tide-dominated scenario, overtopping occurs in three tributaries, which is caused by the jacking role of the sea. ②The working condition of the dispersed drainage scheme can reduce the waterlogging area by 37.78% and 74.6% under the flood-dominated and tide-dominated scenarios respectively, and shorten the flood-affected duration by 24.53% and 51.61% respectively. Under the tide-dominated scenario, the overtopping of the aforementioned three tributaries can be solved through the dispersed drainage. ③When a flood occurs, through the opening of three dispersed drainage pumping stations and the estuary sluice the flood can flow out to the sea. When an extremely high tide occurs, through the closing of the estuary sluice and the opening of the estuary pumping station, the water level of the main river can be lowered, which solves the problems of flooding prevention and drainage. The research results can provide a basis for drainage schemes in high-density built-up areas, which plays an important role in ensuring urban safety.